IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAME TOURNAMENT (TGT) BERBANTUAN MEDIA GAME EDUKASI QUIZ BERBASIS CANVA UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF MATEMATIKA KELAS V MATERI PECAHAN CAMPURAN DI SD NAMIRA KRAKSAAN - Desvita Sania Putri; Didit Yulian Kasdriyanto; Ryzca Siti Qomariyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Based on observation is the lack of learning media and the absence of interactive media. So that students find it difficult to learn mathematics, students have decreased to learning outcomes. This study aims to find out how the implementation of the Cooperative Learning Model type Teams Game Tournament (TGT) assisted by Canva -based educational game media to improve the cognitive abilities of Mathematics Class V SD Namira Kraksaan. His research method uses Classroom Action Research (CAR) The subject of this study is class V with a number of Sisswa of 21 people. Actions given to research subjects to improve students' cognitive abilities in mathematics by applying the Game Tournament Teams (TGT) model that uses Canva -based educational game media.The results showed that the application of the Teams Game Tournament (TGT) learning model using Canva -based educational game media could improve student learning outcomes. This is indicated by an increase in the results of the value achieved each meeting. In the first cycle the first meeting was known to the completion of the completed student which was 42.5 % and the second meeting of the percentage of students was complete, namely 61.90 %. Whereas in the second cycle there was an increase in learning outcomes, namely the percentage of students complete, namely 85.71%. Based on the results of the research above it can be concluded that the TEAMS Game Tournament (TGT) model uses Canva -based educational game media to improve students' cognitive abilities.